Guyana : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2001)
The statistical data on value added by sector at current prices, value added by sector at constant prices, GDP by expenditure at current prices, consumer prices, population estimates, employment in the public sector, summary of the operations of the public sector and operations of the central government of Guyana are presented in this paper. The data on monetary survey, accounts of the bank of Guyana, value, price, and volume indices for exports and imports commodity, and related economic indices are also presented.